Analisis Spasial pada Model Perekonomian Sumatera Bagian Selatan - Ukhti Ciptawaty (Jurnal Ekonomi Pembangunan, 2021)
This study tries to use the Spatial concept by analyzing the observed spatial patterns and spatial autocorrelation, as well as evaluating the spatial modeling of each region in 60 districts/cities in five Southern Sumatra Provinces. This research used Geoda. Geoda will then provide a spatial description of the condition of the percentage of GRDP presented in the Moran I statistics, LISA and LISA Clusterd Map in 2015-2019. The results of this study are expected to show the spatial relationship of GRDP between 60 regencies/cities in five provinces in Sumbagsel and be able to indicate how the spatial relationship is in the clustered pattern of regions with the same characteristics. Furthermore, the LISA Cluster map is expected to describe the grouping of GRDP in 11 regions. The SAR model was chosen to analyze cases of spatial linkage. This study will further provide an economic analysis of how the percentage of the population and GRDP influence, In addition, this study will examine how the influence of the Development Index and poverty on GRDP. Therefore, this research will be one of the studies that has the latest updates because it uses two approaches; spatial approach and economic approach presented in the results of the discussion and discussion.